Enhancing Well-Being and Social Connectedness for Māori Elders Through a Peer Education (Tuakana-Teina) Programme: A Cross-Sectional Baseline Study - Oetzel, John G.; Ruru, Stacey; Zhang, Yingsha; Simpson, Mary Louisa; Nock, Sophie; Meha, Pare; Holmes, Kath; Clark, Marama; Adams, Hariata; Akapita, Ngapera; Ngaia, Kawarau; Murphy, Shane; et al. (Frontiers in Public Health, 2021)
Background: Māori kaumātua (elders) face stark health and social inequities compared to non-Māori New Zealanders. The tuakana-teina (older sibling-younger sibling) peer education programme is a strengths-based approach to enhance well-being and social connectedness. The purpose of this study is to present the baseline data from this programme and identify correlates of well-being outcomes. Method: Participants included 128 kaumātua who completed a self-report survey about health-related quality of life, spirituality, social connection and loneliness, life satisfaction, cultural identity and connection, elder abuse, health service utilisation and demographics. Findings: Multiple regression models illustrated the following correlates of outcomes: (a) self-rated health: needing more help with daily tasks (β = −0.36) and housing problems (β = –0.17); (b) health-related quality of life: needing more help with daily tasks (β = –0.31), housing problems (β = –0.21), and perceived autonomy (β = 0.19); (c) spiritual well-being: understanding of tikanga (cultural protocols) (β = 0.32) and perceived autonomy (β = 0.23); (d) life satisfaction: social support (β = 0.23), sense of purpose (β = 0.23), cultural identity (β = 0.24), trouble paying bills (β = –0.16), and housing problems (β = –0.16); (e) loneliness: elder abuse (β = 0.27), social support (β = –0.21), and missing pleasure of being with whānau (extended family) (β = 0.19). Conclusions: Key correlates for outcomes centred on social support, housing problems, cultural connection and perceived autonomy. These correlates are largely addressed through the programme where tuakana/peer educators provide support and links to social and health services to teina/peer recipients in need. This study illustrates needs and challenges for kaumātua, whilst the larger programme represents a strengths-based and culturally-centred approach to address health issues related to ageing in an Indigenous population.